The emblematics of the self : ekphrasis and identity in Renaissance imitations of Greek romance - Bearden, Elizabeth B., 1975- (University of Toronto Press, 2012)
The Emblematics of the Self breaks new ground in understanding hegemonic and cosmopolitan European conceptions of the "other," as well as new possibilities for early modern identities, in an increasingly global Renaissance.